Simultaneous Determination of B1, B2, B3, B6, B9, and B12 Vitamins in Premix and Fortified Flour Using HPLC/DAD: Effect of Detection Wavelength - Y. Albawarshi; A. Amr; K. Al-Ismail; M. Shahein; M. Majdalawi; M. Saleh; A. Khamaiseh; B. El-Eswed (Journal of Food Quality)
Simultaneous determination of water-soluble B vitamins is a troublesome analytical procedure since they have greatly variable structures and acid-base properties which imposed difficulties on eluting them in short time and selecting wavelength of detection. The aim of the present study was to develop a simple method that overcomes these difficulties. The method was successful in simultaneous determination of B1, B2, B3, B6, B9, and B12 in premix and fortified flour by extracting vitamins with 0.1% (w/v) of ascorbate and ethylene diamine tetra-acetic acid (EDTA) solution followed by eluting using gradient mobile phase consisting of 0.03% trifluoroacetic acid aqueous solution (pH 2.6) and acetonitrile on high performance liquid chromatography (HPLC) instrument coupled with diode array detector (DAD). Elution of vitamins was completed within 9.3 min, and the lowest values obtained for limit of quantification (LOQ) for B1, B2, B3, B6, B9, and B12 were 0.6, 0.2, 0.8, 0.3, 0.5, and 0.7 μg/mL, respectively, at four wavelengths of 361, 280, 265, and 210 nm. In general, variation of wavelength of detection in the range from 210 to 361 nm affects sensitivity but had a marginal effect on the linearity and LOQ of the developed method and its application for determining B vitamins in premix and fortified flour. The 210 nm wavelength exhibited the highest sensitivity though resulted in higher values of B vitamins in fortified flour with respect to 265, 280, and 361 nm. Noteworthy, determination of B2 and B12 in the premix at 361 nm had relatively high RSD values compared to the lower wavelengths. Thus, wavelengths in the range from 265 to 280 may be more favorable over 210 and 361 nm. The method reported in the present work does not require any sample cleanup/preconcentration steps, and chromatographic elution was achieved in 9.3 min without the need for ion-pairing reagents.